POLITIK LUAR NEGERI REPUBLIK INDONESIA MASA LAMPAU, KINI DAN MASA DEPAN : SUATU TINJAUAN DAN SARAN KEDEPAN - Aiyub Mohsin (Universitas Nasional, 2019)
The Foreign Policy can be defined as a policy and/or action pursued by a government in dealing with other state’s government in order to achieve its national objectives, especially to safeguard its national interests abroad. The Foreign Policy of the Republic of Indonesia is a policy and/or an action to purposedly design by the government of Indonesia to achieve its national objectives especially to safeguard its national interest abroad. The guiding principal which serve in Indonesia’s Foreign Policy excecution is to pursue an independent and active line. The meaning of Independent is the Republic of Indonesia should not join to any political bloc or military pact, however it should be “Active to participate in creating a world peace based on freedom, lasting peace and social justice” (4th paragraph of the Indonesian 1945 constitution preambule). From the time’s point of view, the Indonesia’s foreign policy could be divided into five periods: 1) The period of Independent Struggle (1945-1950); 2) Paliamentary Democracy period (1950 —1959); 3) The period of Guided Democracy (1959-1965); 4) New Order periode (1966-1998); 5) The periode of Reformation (1998 – until now). The execution of foreign policy by the Indonesia’s government in any period through or by diplomacy, taking into account the current issue(s), strategic environment and the agenda priorities which should be accomplished